Emotional Labor in the Dual Role of Teaching and Coaching. Issue 5 (October 2018) - Lee, Ye Hoon; Chelladurai, Packianathan; Kang, Chanho
This study investigated the emotional labor involved in two forms of sport services—teaching and coaching—as perceived by high school teacher–coaches regarding required emotional displays and the use of emotional labor strategies. A total of 403 high school teacher–coaches from 47 states in the United States completed the online questionnaires measuring their perceptions of required emotional displays and their uses of emotional labor strategies in the two occupational roles. Results showed that there was no significant difference in the perception of positive emotional displays as required among participants. However, participants perceived that the expressions of friendliness and cheerfulness were more required in teaching than in coaching. On the other side, negative emotional displays were perceived to be more required in coaching than in teaching. That is, expressing upset, disappointment, anger, unhappiness, and frustration were perceived differently among participants. Also, participants utilized more surface acting when teaching and employed more genuine expression when coaching. The findings of this study highlight that differences do exist in the perception of required emotional displays and the utilization of emotional labor strategies in the two roles of teaching and coaching. These results were discussed in light of the task and group differences between teaching and coaching.